Quality of life after lumbar microsciopic discectomy - Koirala, Sagar; Lohani, Subhash; Bishokarma, Suresh; Koirala, Sharad; Shrestha, Pratyush (Nepal Journal of Neuroscience, 2021)
Introduction Lumbar disc herniation also known as prolapsed intervertebral disc is one of the well-known causes of low back pain. Among various modalities of treatment, surgery is often kept as the last resort when conservative treatment fails. Conventional surgical methods have been replaced by minimally invasive surgeries like microscopic, endoscopic and percutaneous lumbar discectomy in the hopes of decreasing post-operative pain. However, it is not uncommon for patient to have residual pain even after discectomy. Patients also complains of reduced quality of life (QOL). SF-36 is a standardized questionnaire for measuring QOL. Few studies have used this questionnaire to look into QOL of these patients but no such study is available in Nepalese perspective. Materials and Methods A prospective cross-sectional study was conducted among all patients undergoing single level unilateral microscopic lumbar discectomy in Upendra Devkota Memorial National Institute of Neurological Sciences from February 1st 2017 to January 31 2018. After taking informed consent, subjects were asked to respond to the preformed questionnaire and SF-36 survey. Interviews were individually conducted by the same investigator at two different time points: i) before lumbar discectomy. ii) 3 months after lumbar discectomy. QOL scores before and after were compared. Results Total of 50 patients meeting the inclusion criteria were studied. The mean age of the study group was 38.7 ± 9.9 years with male preponderance of 76%. The median duration of exacerbation of symptoms was 4 weeks. Along with pain, 64% had sensory deficit whereas 52% had motor deficit. Surgery led to significant improvement in pain score as well as marked improvement of SF 36 quality of life score at 3 months of surgery. However, age, gender, duration of symptoms or presence of sensory or motor deficit before surgery did not predict improvement in overall QOL. Conclusion Patients undergoing microscopic lumbar discectomy for prolapsed intervertebral disc have significant improvement in pain score and QOL after 3 months of surgery.